Role of amino acids in translational mechanisms governing milk protein synthesis in murine and ruminant mammary epithelial cells - Yana Moshel; Robert E. Rhoads; Itamar Barash (2006)
Abstract The role of amino acids (AA) on translational regulation in mammary epithelial cells cultured under lactogenic conditions was studied. The rates of total protein synthesis and β‐lactoglobulin (BLG) synthesis in mouse CID‐9 cells were 2.1‐ or 3.1‐fold higher, respectively, than in their bovine L‐1 counterparts. Total AA deprivation or selective deprivation of Leu had a negative protein‐specific effect on BLG synthesis that was more pronounced in bovine cells than in murine cells. Dephosphorylation of eukaryotic initiation factor 4E‐binding protein 1 (4E‐BP1) and S6 kinase (S6K1) on Thr 389 but not on Ser 411 was also more prominent in bovine cells. Noteably, deprivation of Leu had a less marked effect on BLG synthesis and 4E‐BP1 or S6K1 phosphorylation than deprivation of all AA. In AA‐deprived CID‐9 cells, Leu specifically restored BLG synthesis from pre‐existing mRNA whereas AA also restored total protein synthesis. This restoration was associated with a more pronounced effect on 4E‐BP1 and S6K1 phosphorylation in bovine versus murine cells. Rapamycin specifically reduced Leu‐ and AA‐stimulated BLG translation initiation in a dose‐dependent manner. A further reduction was observed for Leu‐treated cells in the presence of LY294002, a PI3K (phosphatidylinositol 3‐kinase) inhibitor, which also reduced total protein synthesis. These findings suggest that direct signaling from AA to the translational machinery is involved in determining the rates of milk protein synthesis in mammary epithelial cells. J. Cell. Biochem. 98: 685–700, 2006. © 2006 Wiley‐Liss, Inc.